Comparative analysis of two kinds of garlic seedings: qualities and transcriptional landscape - Penghui Ai; Jundong Xue; Yifei Zhu; Wenchao Tan; Yifei Wu; Ying Wang; Zhongai Li; Zhongya Shi; Dongru Kang; Haoyi Zhang; Liwen Jiang; Zicheng Wang (BMC Genomics, 2023)
Abstract Background Facility cultivation is widely applied to meet the increasing demand for high yield and quality, with light intensity and light quality being major limiting factors. However, how changes in the light environment affect development and quality are unclear in garlic. When garlic seedlings are grown, they can also be exposed to blanching culture conditions of darkness or low-light intensity to ameliorate their appearance and modify their bioactive compounds and flavor. Results In this study, we determined the quality and transcriptomes of 14-day-old garlic and blanched garlic seedlings (green seedlings and blanched seedlings) to explore the mechanisms by which seedlings integrate light signals. The findings revealed that blanched garlic seedlings were taller and heavier in fresh weight compared to green garlic seedlings. In addition, the contents of allicin, cellulose, and soluble sugars were higher in the green seedlings. We also identified 3,872 differentially expressed genes between green and blanched garlic seedlings. The Kyoto Encyclopedia of Genes and Genomes analysis suggested enrichment for plant-pathogen interactions, phytohormone signaling, mitogen-activated protein kinase signaling, and other metabolic processes. In functional annotations, pathways related to the growth and formation of the main compounds included phytohormone signaling, cell wall metabolism, allicin biosynthesis, secondary metabolism and MAPK signaling. Accordingly, we identified multiple types of transcription factor genes involved in plant-pathogen interactions, plant phytohormone signaling, and biosynthesis of secondary metabolites among the differentially expressed genes between green and blanched garlic seedlings. Conclusions Blanching culture is one facility cultivation mode that promotes chlorophyll degradation, thus changing the outward appearance of crops, and improves their flavor. The large number of DEGs identified confirmed the difference of the regulatory machinery under two culture system. This study increases our understanding of the regulatory network integrating light and darkness signals in garlic seedlings and provides a useful resource for the genetic manipulation and cultivation of blanched garlic seedlings.